THE HOLISTIC EDUCATION MODEL AS A FRAMEWORK FOR SUSTAINABLE LEARNING IN MODERN EDUCATIONAL SYSTEMS - Iqbal Amar Muzaki; Amirudin Amirudin; Fatimah Az Zahro; Nur Sobarie (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to analyze and explain the holistic education paradigm at Islamic Boarding School, with a focus on the implementation of a sustainable modern education model based on spiritual values. This study used a descriptive qualitative approach involving Al-Bahjah lecturers as informants, as well as collecting data through in-depth interviews, observation, and documentation. Data analysis was conducted using the Miles and Huberman technique, which included data reduction, data presentation, and conclusion drawing and verification, accompanied by source triangulation to test data validity. The results showed that Al-Bahjah Islamic Boarding School implements an educational pattern that balances religious knowledge mastery, academic competency development, and selective technology utilization based on morals. This strategy was realized through internal empowerment, the involvement of external experts, and the application of student-centered learning that fosters the independence of students. This study concluded that Islamic boarding schools had the capacity to serve as holistic education models that were able to adapt to modernity while maintaining their spiritual values as the main foundation of Islamic education. These findings indicated that the holistic education model applied at Al-Bahjah provided a meaningful framework for integrating tradition and modernity in Islamic education. Practically, this study highlighted the importance of character-based technology integration and continuous teacher development as key strategies to ensure the sustainability and relevance of Islamic education in the digital era.